(untitled) (Journal of Computational Mathematics, 2001)
Based on domain decomposition, we give two multiplicative schwarz methods with time stepping along characteristic for semi-linear, convection diffusion parabolic problems. We give some a priori error estimates, which tell us that the convergence of the approximate solution is independent of the iteration times at every time-level. Finally we give some numerical examples.